A simple method for chromium speciation analysis in contaminated water using APDC and a pre-heated glass tube followed by HPLC-PDA - Salihu, Simon Olonkwoh (Elsevier, 2018)
In this study, a simple sample preparation method was developed for the determination of tri-and hexavalent chromium in water samples. It utilizes a pre-heated customized glass tube (CGT), to supply the heat energy required for the reaction of Cr(III) with ammonium pyrrolidinedithiocarbamate (APDC). The products of the Cr complexes, tris(1-pyrrolidinecarbodithioato)chromium(III) and bis(1-pyrrolidinecarbodithioato)[1-pyrrolidinecarbodithio(thioperoxoato)]chromium(III) were chromatographed with Shimadzu LC-20AT and Zobax Eclipse C18 (150 mm × 4.6 mm, 5 µm) column using ACN: Water, (7:3, v/v) as the mobile phase. The concentration of Cr(III) ranged from 0.06 mgL−1 to 0.09 mgL−1 and that of Cr(VI) was between 0.02 mg L−1 to 0.04 mgL−1 in the samples. Percentage recoveries from spiked real samples were between 87% (tap water) to 110% (wastewater) for Cr(III) and 92% (pond water) to 117% (tap water) for Cr(VI). The limits of detection (LODs) were 0.0029 mg L−1 and 0.0014 mg/L−1 for Cr(III) Cr(VI) respectively. While the limits of quantitation (LOQs), were 0.0098 mg L−1 and 0.0047 mg L−1 for Cr(III) and Cr(VI) respectively. Method precision (RSD (%)) was 3.3% and 3.5% for Cr(III) and Cr(VI) respectively. The developed method was applied for the speciation analysis of chromium in drinking water, tap water, wastewater, river water, and pond water samples. Our findings proved the method is simple and inexpensive. The method was validated by the analysis of a certified reference material (CRM) SLRS-4. The percentage recovery and RSD(%) from the spiked CRM were 91% and 115% and 0.32% and 1.4% for Cr(III) and Cr(VI) respectively.